Contrastive Linguistics and Translation Studies Interconnected: The Corpus-based Approach - Ramón García, Noelia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The relationship between contrastive linguistics (CL) and translation studies (TS) as two disciplines within the field of applied linguistics has been explored in depth by several authors, especially in the 1970s and early 1980s. From the mid-nineties on both these disciplines have experienced a great boom due to the use of computerised language corpora in linguistic analysis. We will argue in this paper that this new corpus-based approach to CL and TS makes it necessary to revise the relationship between them, and look for a new common ground to work on. Our hypothesis is that the use of translation equivalence as a tertium comparationis for a corpus-based contrastive analysis provides essential data for TS in a wide range of aspects. On the other hand, the corpus approach of TS has shed a new light on numerous aspects of CL.